2011
DOI: 10.5194/hess-15-561-2011
|View full text |Cite
|
Sign up to set email alerts
|

Desert shrub stemflow and its significance in soil moisture replenishment

Abstract: Abstract. Stemflow of xerophytic shrubs represents a significant component of water replenishment to the soil-root system influencing water utilization of plant roots at the stand scale, especially in water scarce desert ecosystems. In this study, stemflow of Caragana korshinskii was quantified by an aluminum foil collar collection method on re-vegetated sand dunes of the Shapotou restored desert ecosystem in northwestern China. Time domain reflectometry probes were inserted horizontally at 20 different soil p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 21 publications
6
48
0
3
Order By: Relevance
“…This study showed that shrub stemflow conserved in the deep soil layers can be an available moisture source for plant growth under arid conditions and that root channels were preferential pathways for the movement of most stemflow water into the soil. Similar experiments by Pan and Wang (2009) and Wang et al (2011b) gave consistent results. Small rainfall events usually affect only the uppermost cm of the soil and easily lost through direct evaporation, and the soil moisture was therefore mainly contributed by the large events (Schwinning and Sala, 2004).…”
Section: Introductionsupporting
confidence: 78%
“…This study showed that shrub stemflow conserved in the deep soil layers can be an available moisture source for plant growth under arid conditions and that root channels were preferential pathways for the movement of most stemflow water into the soil. Similar experiments by Pan and Wang (2009) and Wang et al (2011b) gave consistent results. Small rainfall events usually affect only the uppermost cm of the soil and easily lost through direct evaporation, and the soil moisture was therefore mainly contributed by the large events (Schwinning and Sala, 2004).…”
Section: Introductionsupporting
confidence: 78%
“…The special hydrological and physical characteristics of BSC improved and promoted the soil microhabitats in desert areas and increased water holding capacity. The higher unsaturated hydraulic conductivity under low soil matric potential conditions could improve soil water availability in the shallow layers, which would improve the survival rates of some shallow rooted shrubs and herbs and small soil animals in the sand-binding vegetation communities [20,[30][31][32]. It may even lead to an increase in population size.…”
Section: Influences Of Bsc On Various Hydrological Processesmentioning
confidence: 99%
“…Stemflow by C. korshinskii accounted for 69% of the annual rainfall volume, Around 2.2 mm precipitation was necessary to generate stemflow in the shrub stand which meant that stemflow occurred in 34% of the rain events that happened over the year. Stemflow accounted for 8% of gross precipitation and the average funneling ratio was as high as 90 [20].…”
Section: Rainfall Interception and Redistribution By Sandbinding Shrubsmentioning
confidence: 99%
See 1 more Smart Citation
“…The double-funnelling effects of stemflow and preferential flow create "hot spots" and "hot moments" by enhancing nutrient cycling rates at the surface soil matrix (Mcclain et al, 2003;Johnson and Lehmann, 2006;Sponseller, 2007), thus substantially contributing to the formation and maintenance of "fertile islands" (Whitford et al, 1997), "resource islands" (Reynolds et al, 1999) or "hydrologic islands" (Rango et al, 2006). This effect is important for the normal function of rainfed dryland ecosystems (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%